Regional Poverty and Its Determinants in Iran - Shooshtarian, Ashan; Bakhshoodeh, Mohammad (Journal of Income Distribution®, 2009)
Household data were used in this study to measure regional povertyand its determinants separately for ten defined zones in rural and urbanareas in Iran in 2005. The non-parametric approach was used toestimate poverty lines for each zone and the effect of poverty determinantson poor and non-poor households was studied applying probitmodels. The findings indicate that poverty rate, gap, and intensity arehigher in the urban areas. Family size, level of literacy, and asset ownershipare amongst the various determinants of poverty. In general,the success of antipoverty programs depends highly on recognition ofregional differences.